Perinatal mental health among South Asian immigrant women in Canada: A scoping review protocol - Bibi Hajira; Kimberley Jackson; Roula Kteily Hawa; Anam Shahil-Feroz (PLoS ONE, 2026)
Perinatal mental health concerns are common and may be heightened among immigrant populations because of migration-related stressors, social isolation, stigma, language barriers, and limited access to culturally safe care. Although previous reviews have examined perinatal mental health among immigrants broadly, evidence focused specifically on South Asian immigrant women in Canada across pregnancy and the postpartum period has not been comprehensively mapped. South Asian women represent one of the largest and fastest-growing immigrant populations in Canada and may experience unique cultural, familial, linguistic, and migration-related factors that shape perinatal mental health experiences and access to care. This scoping review will map the extent, range, and nature of evidence on perinatal mental health among South Asian immigrant women in Canada by examining reported mental health outcomes, associated risk and protective factors, help-seeking experiences, and barriers and facilitators to accessing support services, and identify gaps to inform future research, practice, and policy. This protocol was developed in accordance with Joanna Briggs Institute guidance for scoping review protocols and reported using the PRISMA-P checklist, where applicable (see S2 Checklist). The completed scoping review will be reported according to the PRISMA-ScR checklist. MEDLINE, Embase, PsycINFO, CINAHL, and Scopus will be searched for literature published from January 2000 to the date of the final search. Grey literature will be identified through targeted searches of government, public health, professional, and community organization websites. Eligible sources will include qualitative, quantitative, mixed-methods, and relevant grey literature addressing perinatal mental health during pregnancy and up to 12 months postpartum among South Asian immigrant women residing in Canada. Inclusion criteria are immigrant women of South Asian origin from counties such as India, Pakistan, Bangladesh, Sri Lanka, Afghanistan, Nepal, Bhutan, and Maldives residing in Canada during the perinatal period. Two reviewers will independently screen titles, abstracts with disagreements resolved through discussion or third-reviewer adjudication. Data will be extracted using a standardized charting form and summarized using descriptive mapping and narrative synthesis. Protocols and planned studies will be charted separately from completed studies. Consistent with scoping review methodology, formal exclusion of studies based on methodological quality will not be undertaken; however, study characteristics and reported methodological limitations will be charted to support interpretation of the evidence base. Ethics approval is not required because the review will use publicly available sources only. Findings will be disseminated through a dissertation, peer-reviewed publication, and conference presentations. The review will provide a comprehensive overview of existing evidence and knowledge gaps to support culturally responsive perinatal mental health research, policy development, and healthcare practice for South Asian immigrant women in Canada. This protocol has been preregistered on the Open Science Framework:10.17605/OSF.IO/FZN4S.